Discrimination, Internalized Homonegativity, and Attitudes Toward Children of Same‐Sex Parents: Can Secure Attachment Buffer Against Stigma Internalization?. Issue 3 (8th October 2016) - Trub, Leora; Quinlan, Ella; Starks, Tyrel J.; Rosenthal, Lisa
Abstract : With increasing numbers of same‐sex couples raising children in the United States, discriminatory attitudes toward children of same‐sex parents (ACSSP) are of increasing concern. As with other forms of stigma and discrimination, lesbian, gay, and bisexual (LGB) individuals are at risk for internalizing these societal attitudes, which can negatively affect parenting‐related decisions and behaviors and the mental and physical health of their children. Secure attachment is characterized by positive views of the self as loveable and worthy of care that are understood to develop in early relationships with caregivers. Secure attachment has been associated with positive mental and physical health, including among LGB individuals and couples. This study aimed to test the potential buffering role of secure attachment against stigma internalization by examining associations among secure attachment, discrimination, internalized homonegativity (IH), and ACSSP in an online survey study of 209 U.S. adults in same‐sex relationships. Bootstrap analyses supported our hypothesized moderated mediation model, with secure attachment being a buffer. Greater discrimination was indirectly associated with more negative ACSSP through greater IH for individuals with mean or lower levels, but not for individuals with higher than average levels of secure attachment, specifically because among those with higher levels of secure attachment, discrimination was not associated with IH. These findings build on and extend past research, with important implications for future research and clinical work with LGB individuals, same‐sex couples, and their families, including potential implementation of interventions targeting attachment security.